Changes of Physical Function and Quality of Life in Patients with Type 2 Diabetes after Exercise Training in a Municipality or a Hospital Setting - Stig Molsted; Trine Munk Jensen; Jane Sedum Larsen; Louise Bockhoff Olesen; Sofie Bjerre Milling Eriksen; Thomas Rehling; Signe Sætre Rasmussen; Mette Aadahl (Journal of Diabetes Research)
Introduction. The aim was to compare changes in physical function and quality of life (QOL) after an exercise training programme to patients with type 2 diabetes mellitus (T2DM) in a municipality and a hospital setting and to compare the patients’ physical function and QOL with an age- and sex-matched general population. Methods. Patients with T2DM were stratified to exercise training in a municipality (n=26) or a hospital (n=46), respectively. The training was one hour twice weekly for 12 weeks. The outcomes were physical function (30 sec chair stand test (CST)) and QOL (using the SF-36). The data for the general population were collected from previous reference studies. Results. Fifty-one (71%) participants completed the intervention. The CST results improved in both groups with no difference between the municipality and hospital groups (1.6 [0.1; 3.1] vs. 3.5 [2.3; 4.8] no., respectively, p=0.062). The QOL scales physical function and general health increased more in the municipality group than in the hospital group (10.5 [2.8; 18.2] vs. -1.2 [-7.9; 5.5], respectively, p=0.031, and 8.3 [2.3; 14.4] vs. -0.2 [-5.6; 5.1], respectively, p=0.042). Dropout (n=21) during the intervention was associated with reduced QOL at baseline. The patients’ CST results at baseline were reduced compared to the general population (11.8±3.5vs.18.9±3.3, respectively, p<0.001). All QOL scales apart from social function were reduced in the patients compared to the general population. Conclusion. Patients in a 12-week exercise training programme in a hospital or a municipality setting had significantly lower QOL compared to an age- and sex-matched population sample. Similar improvements in physical function were observed in patients after completion of the exercise programme irrespective of exercise setting, whereas patient exercising in a municipality setting had higher positive changes in QOL than patients undergoing the same exercise programme in a hospital setting.